Indigenous children and receipt of hospital dental care in Australia - L. M. JAMIESON & K. F. ROBERTS-THOMSON (Paediatric Dentistry, 2006)
The aim of this study was to investigate dental procedures received under hospital general anaesthetic by indigenous and non-indigenous Australian children in 2002–2003.